The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1002/zaac.200700376
|View full text |Cite
|
Sign up to set email alerts
|

M2B5 or M2B4? A Reinvestigation of the Mo/B and W/B System

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
99
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 18 publications
10
99
1
Order By: Relevance
“…Rietveld a) Maximum residual electron density is found at the origin of the cell, but residual neutron scattering is very low at that position. [29], which are even more similar to ReB 2 . Their crystal structures again consist of alternating layers of metal and boron atoms, hence the boron atom layers are alternating planar (as in AlB 2 ) or corrugated (as in ReB 2 ).…”
Section: Resultsmentioning
confidence: 68%
“…Rietveld a) Maximum residual electron density is found at the origin of the cell, but residual neutron scattering is very low at that position. [29], which are even more similar to ReB 2 . Their crystal structures again consist of alternating layers of metal and boron atoms, hence the boron atom layers are alternating planar (as in AlB 2 ) or corrugated (as in ReB 2 ).…”
Section: Resultsmentioning
confidence: 68%
“…ReB 2(hex) (Figure 8), W 2 B 4(hex) ("W 2 B 5(hex) "; note that while the structure is referred to as having a "W 2 B 5(hex) " structure, it has been shown more recently that the stoichiometry is W 2 B 4; [177] Figure 10) are similar to the AlB 2 structure and have either regular or deformed two-dimensional boron layers. W 2 B 4(hex) (previously "W 2 B 5(hex) ") and Mo 2 B 4(rhomb) (previously "Mo 2 B 5(rhomb) ") differ in the alternation order of metal layers.…”
Section: Of 29) 1604506mentioning
confidence: 99%
“…[173] Note that while the structure is referred to as having a "W 2 B 5(hex) " structure, it has been shown recently that the stoicheometry is W 2 B 4 . [177] Boron atoms are in gray, metal atoms are in dark gray. Figure 10.…”
Section: Figurementioning
confidence: 99%
“…This last structure has been included because first principles calculations have shown that this structure could be stable at high pressure in the cases of TiB 2 [3] and MoB 2 [4] compounds. The characteristics of the structures considered in the present work are given in Table 1 [5][6][7][8][9][10][11][12][13]. [14].…”
Section: Introductionmentioning
confidence: 99%